Pencegahan Infeksi Arbovirus dengan Tanaman Pengusir Nyamuk dan Raket Pembunuh Nyamuk - Anak Agung Dewi Megawati; Ni Wayan Widhidewi; Ayu Savitri Siskayani; Erly Sintya; I Gusti Made Arjana (Community Service Journal (CSJ), 2026)
Mosquito-borne diseases (arboviruses) such as dengue, chikungunya, and Japanese encephalitis remain major public health challenges in Bali, where incidence rates continue to rise. The Community Partnership Program (PKM) conducted by the Faculty of Medicine and Health Sciences, Warmadewa University, aims to strengthen community capacity in preventing arboviral infections through an environmentally based and community empowerment approach. The program focuses on PKK (Pemberdayaan dan Kesejahteraan Keluarga) women at Bangli Regency as key agents of change through education, training in cultivating mosquito-repellent plants, and the provision of vector control tools such as electric mosquito rackets. The implementation methods include pre-tests, educational sessions, hands-on training, and post-activity monitoring. The results showed an increase in participants’ knowledge by approximately 39%, along with positive behavioral changes in applying 3M Plus–based prevention practices. This approach aligns with the achievement of the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being) through the prevention of infectious diseases, SDG 5 (Gender Equality) by empowering women as community health agents, and SDG 13 (Climate Action) through sustainable, environmentally based vector control strategies. By integrating community education, environmental interventions, and scientific innovation, this program has the potential to serve as a sustainable translational model for controlling mosquito-borne diseases in Indonesia.